Стереохимия присоединения к фенил-ацетилену. Структура и кинетика кислотного гидролиза цис- и транс- 10- (2-фенилвинил) фенотиазинов - Анфиногенов В. А. Виталий Александрович; Напилкова О. А. Ольга Александровна; Сироткина Е. Е. Екатерина Егоровна; Филимонов В. Д. Виктор Дмитриевич; Хлебников А. И. Андрей Иванович (1984, 1984)
Деп. в ОНИИТЭХим, г. Черкассы, 28.12.84, № 1202-ХП-84.